Investigation of antioxidative and cell signaling properties of bioactive compounds from aromatic herbs - Miloš, Mladen (Bulletin of Chemists and Technologists of Bosnia and Herzegovina, 2014)
Study focuses on isolating and testing bioactive compounds from aromatic herbs for antioxidant activity and enzyme inhibition. The research employs extraction, fractionation, and chromatographic separation followed by spectroscopic analysis. Applications target development of natural remedies and functional foods.